(3dGejI GdYLe (B- (3bUjOIs - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3CUGdI GdQCj UGfJfj dOi GdNWd hMdjoI GdaVd RGfJfj dOi GdYWd s
(3BNQgG (B:s
(3bO QTMhc dCeQ Ef aWfJ dog aGQHC HfaSc Cf JQYi eY Gdged s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdNW ajg VHWs
(3hQO CjVkG JMJ Qbe (B2182s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B159 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs